Expert consensus statement on the perioperative management of adult patients undergoing head and neck surgery and free tissue reconstruction from the Society for Head and Neck Anesthesia. Issue 2 (14th December 2021) - Healy, David W.; Cloyd, Benjamin H.; Straker, Tracey; Brenner, Michael J.; Damrose, Edward J.; Spector, Matthew E.; Saxena, Amit; Atkins, Joshua H.; Ramamurthi, Radhamangalam J.; Mehta, Arpan; Aziz, Michael F.; Cattano, Davide; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The perioperative care of adult patients undergoing free tissue transfer during head and neck surgical (microvascular) reconstruction is inconsistent across practitioners and institutions. The executive board of the Society for Head and Neck Anesthesia (SHANA) nominated specialized anesthesiologists and head and neck surgeons to an expert group, to develop expert consensus statements. The group conducted an extensive review of the literature to identify evidence and gaps and to prioritize quality improvement opportunities. This report of expert consensus statements aims to improve and standardize perioperative care in this setting. The modified Delphi method was used to evaluate the degree of agreement with draft consensus statements. Additional discussion and collaboration was performed via video conference and electronic communication to refine expert opinions and to achieve consensus on key statements. Thirty-one statements were initially formulated, 14 statements met criteria for consensus, 9 were near consensus, and 8 did not reach criteria for consensus. The expert statements reaching consensus described considerations for preoperative assessment and optimization, airway management, perioperative monitoring, fluid management, blood management, tracheal extubation, and postoperative care. This group also examined the role for vasopressors, communication, and other quality improvement efforts. This report provides the priorities and perspectives of a group of clinical experts to help guide perioperative care and provides actionable guidance for and opportunities for improvement in the care of patients undergoing free tissue transfer for head and neck reconstruction. The lack of consensus for some areas likely reflects differing clinical experiences and a limited available evidence base.